Principles of marketing - Kotler, Philip; Armstrong, Gary (Pearson Education, 2014)
Enphasizes the importance of the brand: increased brand focus. Highlights the social media revolution: new interactive and social media discussions. New emphasis on enduring principles in a changing industry. focus on ethics: new principled practice boxes.